Country-level impact of climate change on maternal and newborn health: Associations between temperature, precipitation, maternal mortality, stillbirth, and neonatal mortality in the Democratic Republic of the Congo - Carrie J. Ngongo; Donal Bisanzio; Gabriella Corrigan; Karl B. Angendu; Alisha Smith-Arthur; Brian Hutchinson; Pierre Akilimali (Environment International)
Background: Evidence connecting extreme heat to maternal and newborn health outcomes is needed at country level, especially in tropical areas. DHIS2 (District Health Information Software 2) collects aggregated population health data by health zone in the Democratic Republic of the Congo (DRC). Methods: Drawing from DHIS2 records of 22·7 million DRC births 2018–2023, spatio-temporal modeling assessed associations between maternal mortality, stillbirth, and neonatal mortality and same-month, remotely sensed temperature, precipitation, anomalous high temperature (>95th percentile), and anomalous heavy precipitation (>95th percentile), controlling for month, year, remoteness, and health zone. Findings: Temperatures > 34 °C and anomalous heavy precipitation were strongly associated with increases in same-month stillbirth and maternal mortality and less strongly associated with neonatal mortality. The stillbirth rate rose by 2·3/1,000 births for every degree increase above 34 °C (95% CI: 1·9; 2·5) or by 5·9/1,000 births in months > 95th percentile (32·9 °C; 95% CI: 5·1; 6·7). Maternal mortality rose by 27·3 deaths/100,000 live births for every degree increase above 34 °C (95% CI: 19·1; 35·7) or by 95·3 deaths/100,000 live births in months > 95th percentile (95% CI: 71·3; 119·4). Months with anomalous heavy precipitation were associated with an increase of 5·4 stillbirths/1,000 births (95% CI: 4·8; 6·2) and with 120 maternal deaths/100,000 live births (95% CI: 100·9; 139·5). Interpretation: DHIS2 data offer a readily available opportunity to assess associations between climate and country-level population health outcomes. Further work is needed to hone and evaluate effective approaches that protect mothers and newborns in the face of projected warming and rainfall changes. Risk-based planning, geographic targeting, and stakeholder coordination will support appropriate, context-specific responses.